(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of teaching mathematics using the (I.O.F.P.P) strategy on achievement. To achieve the research objective, the experimental research method was adopted, and the quasi-experimental design of two equivalent groups with a post-test was used to measure achievement. The research community was determined as fifth-grade primary school students in the primary schools of boys affiliated with the General Directorate of Education in Maysan Governorate / Qalaat Saleh District from the academic year 2023-2024 AD. The research sample was formed by intentional selection from students of (Qurtuba Primary School for Boys) and their number reached (61) students, with (31) students in the experimental group who studied mathematics using the (I.O.F.P.P) strategy and (30) students in the control group who studied the same subject in the usual way. The two groups were rewarded with variables (intelligence, chronological age calculated in months, previous achievement in mathematics, previous knowledge in mathematics, and parents’ educational level). The researcher prepared an achievement test in mathematics according to Bloom’s six levels of the cognitive domain, consisting of (20) objective multiple-choice paragraphs with four alternatives. Its validity was verified, and using the Kuder-Richardson equation (KR-20), its reliability coefficient value reached (0.86).After completing the experiment, the tool was applied to the research sample, and after collecting the data and processing it statistically using the t-test for two independent samples, the results showed statistically significant differences between the average scores of the students of the two groups (experimental and control) in the achievement test in mathematics in favor of the experimental group. In light of the research results, the researcher presented a set of recommendations and suggestions that the researcher hopes to study and take into account.